Distinguishing features of high altitude negative leaders as observed with LOFAR - Scholten, O.; Hare, B. M.; Dwyer, J.; Liu, N.; Sterpka, C.; Buitink, S.; Corstanje, A.; Falcke, H.; Huege, T.; Hörandel, Jörg R.; Krampah, G. K.; Mitra, P.; et al. (Atmospheric Research, 2021)
We present high resolution observations of negative leaders at high altitude using the LOFAR radio telescope. We show that the structure of negative leaders at high altitude (altitudes larger than 7 km) differs in several respects from that of negative leaders at lower altitudes. In particular, the High Altitude Negative Leaders (HANLs) show very distinct steps of a few hundred meters, stepping times of the order of a few milliseconds and a filamentary structure that extends outward over several hundreds of meters; as opposed to lower altitude (≲ 5 km) leaders, which have stepping times and distances around 0.01 ms and 10 m. Similar to lower altitude leaders, high altitude leaders emit copious VHF radiation from their propagating tip and have propagation velocities of the order of 105 m/s. Corona-flash like bursts can be distinguished when zooming in to meter and nanosecond scales.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Corona flash; Lightning; LOFAR lightning imaging; Negative leaders; Radio emission; Thunderstorms